2010
DOI: 10.1590/s0036-36342010000800020
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of local and federal smoke-free legislation in Mexico: a longitudinal study among adult smokers

Abstract: Objective To assess the impact of Mexico City and federal smoke-free legislation on secondhand tobacco smoke (SHS) exposure and support for smoke-free laws. Material and Methods Pre- and post-law data were analyzed from a cohort of adult smokers who participated in the International Tobacco Control (ITC) Policy Evaluation Survey in four Mexican cities. For each indicator, we estimated prevalence, changes in prevalence, and between-city differences in rates of change. Results Self-reported exposure to smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 33 publications
(46 reference statements)
4
22
0
2
Order By: Relevance
“…The effect of the smoke-free policies on SHS exposure should be understood in the context of a good tobacco control atmosphere 12 28. A previous study has reported that decreases in self-reported SHS found in Mexico were due to the higher exposure to radio and television smoke-free campaigns, which were aired to support the smoke-free legislation 28.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the smoke-free policies on SHS exposure should be understood in the context of a good tobacco control atmosphere 12 28. A previous study has reported that decreases in self-reported SHS found in Mexico were due to the higher exposure to radio and television smoke-free campaigns, which were aired to support the smoke-free legislation 28.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported that decreases in self-reported SHS found in Mexico were due to the higher exposure to radio and television smoke-free campaigns, which were aired to support the smoke-free legislation 28. To some extent, because of the inadequate enforcement of new tobacco control policies and high exposure to cigarette advertising in Albania, smoking prevalence among males did not decrease, and smoking rates among females and males aged 18–29 years continue to grow, which will lead to more SHS exposure in public places 12.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, debates over local and federal tobacco control policy increased markedly toward the end of 2007,24 when data for the present study were collected. Data collected in 2008, after smoke-free legislation came into force, indicate significant increases in perceived unacceptability of smoking, mostly in Mexico City21 25 but also in other regions of the country 26…”
Section: Discussionmentioning
confidence: 99%
“…Similar bans were put into place in other states between 2011 and 2013, covering 40% of the population. The enforcement level was set to 5 on a 10-point scale based on compliance data from GATS (Instituto Nacional de Salud Pública, 2009) and ITC (Thrasher, Boado, Sebrie, & Bianco, 2009; Thrasher, Nayeli Abad-Vivero, et al, 2012; Thrasher et al, 2010). In compliance with the FCTC, we consider the implementation of complete smoke-free air laws for worksites, bars and restaurants with strong enforcement.…”
Section: Methodsmentioning
confidence: 99%